SISTEM KUNCI ELEKTRONIS DENGAN PEREKAM WAKTU AKSES BERBASIS MIKROKONTROLER AT89C51 - Priyambodo, Sigit; Heironi, Anik (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2014)
The development in technology, especially in electronic technology. Every technology in many fields of study mostly need electronic device. Even door lock incur-porate electronic technology to junction better.To make electronic key system follow few steps. First, the planning to design electronic and mechanic system of the door lock. Second, design the hardware and drill the PCB, Then assemble the electronic compo-nents. Third, design of the software use algoritm from system. Fourth, flash the assembler program into the IC AT89C51 and set it to hardware, next test the completed system.The result, shows that the system can be applied to the door lock system with time recording access. It uses Real Time Clock (RTC), Line Port Terminal (LPT), IC AT89C51 and handphone siemens M35i as the interface system.